Mobile Agents In A Distributed Network With Trusted Node Implementation For Data Protection - Kathirvelkumaran, L; Muralidharan, R (International Journal of Computer Sciences and Engineering, 2019)
Mobile Agents (MA) represents a comparatively new computing pattern which is used in numerous verticals as a means for anatomy disseminated applications. These Mobile Agents are programs which work in such a way that it will work independently by moving from one node to another in order to perform the assigned tasks on behalf of its owner in a distributed network. During which the mobile agents will communicate with the other agents or the hosts in the network and preserves the data when routing between one node and another. But it is difficult for the agents to transfer the preserved data to the home node due to lack of reliability. Thus in this Paper, it is discussed about how the mobile agents can preserve the collected data through a Trusted server or node by allocating a protected space in the trusted node and what are the measures are used for securing the data.